Jolenan Customary Rite as a Religious Culture of Nahdlatul Ulama Communities in Somongari Village, Kaligesing Subdistrict, Purworejo Regency - Deasy Fitriani (Lakpesdam PCNU Kota Salatiga, 2023)
Local traditions in Javanese agrarian communities function as both anchors of socio-religious identity and mechanisms for the reproduction of values through communal rites that connect harmony among humans, nature, and God. Drawing on the framework of customary rites as a social system, the negotiation of modernization, and NU local Islam, this article formulates five research questions: (1) how Jolenan operates as a social system that organizes community relations and reinforces collective identity; (2) how Jolenan’s socio-cultural reproduction unfolds in the face of change/modernization (continuity, adaptation of forms, and sustainability strategies); (3) how Jolenan’s symbolic meanings construct human, God, nature relations within an agrarian rite; (4) how the mechanisms of NU local Islamic integration in Jolenan through the adoption, adaptation, and integration of local-Islamic elements produce religious legitimacy; and (5) what local wisdom values are produced and internalized through social institutions (family, education, economy, village politics, and religion) in sustaining the tradition. The study employs a qualitative approach, using observation, documentation, and the review of relevant interview records (interview journals) as data sources. Data were analyzed descriptively and interpretively through thematic coding aligned with the research questions and by linking the findings to the theoretical framework. The study concludes that Jolenan functions as a social system that structures community relations and consolidates Somongari’s collective identity through patterned, repetitive, and intergenerational ritual practices from preparation to implementation. Its continuity reflects socio-cultural reproduction and adaptive capacity in negotiating modernization, for instance through strengthened performative components and increasingly organized ritual governance, while preserving core values of gratitude, kenduri, and social solidarity. Jolenan’s meanings are articulated through ojo kelalen as an ethic of remembering God within agrarian life, alongside symbols of post-harvest gratitude and communal safety, expressed through kenduri and the communal “distribution of blessings.” Religious legitimacy is achieved as NU local Islam by integrating local symbols and ancestral memory with popular Islamic practices (tahlil, Yasin recitation, shalawat, collective prayers, and almsgiving), enabling the ongoing transmission of local wisdom values through multiple social institutions.